Solutions to logistics challenges faced by fishmongers in handling and distributing processed fish. A case study of Anyanui and Keta Districts of Ghana - Ankoma - Sey, Felicity; Ewedji, Christabel; Adjei, Richard Gyasi; Ahiafakpor, Micheal (Advances in Social Sciences Research Journal, 2020)
The study sought simple indigenous logistics solutions to challenges faced by fishmongers with respect to the handling and distribution of processed fish in the Anyanui and Keta Districts of Ghana. It aimed at designing a handling and distribution unit (HADU) to substitute the conical frustum shaped basket (kenten), which is traditionally used for the purpose. This was a follow-up to a research that sort to curtail identified challenges, including improper stowage, perceived overloading, listing of cargo on transport vehicle, crushing and contamination of the processed fish during transit. Observation, simple mathematical calculations, interviews and experimental testing were employed in the study. The researchers’ considered designing a HADU with characteristics similar to the intermodal ISO container. The HADU was to be appropriate for transporting the processed fish by standard tricycles, trucks, and water crafts. Its volume was calculated to be equivalent to that of the kenten, so as to preserve the measurements of products per unit traditionally supplied to customers, thus not complicating the pricing of contents per unit HADU for the traders. With height 40 cm, length 43 cm and width 56 cm, the resultant cuboidal shaped HADU, had handles, corner posts with extensions and corner fitting spaces. The HADU could be loaded in larger numbers on various sizes of trucks and tricycles compared to the kenten. It also solved the in-transit logistics challenges when stacked at a recommended maximum height of three. Upon its acceptance by the fishmongers, the HADU’s concept was recommended to be sold to basket weavers, to try raw materials other than cane, which will lower its production cost.